The economic/financial biogas feasibility for automotive usage in Toledo´s Region, in Paraná State - Gomes, Ana Carolina Alves (2016)
The production activities in the agricultural sector are highly dependent of several energetic forms and are necessary to the development and implementation of technological alternatives in view of self-supply at reduced costs and lower environmental and social impacts. The significant potential of the use of biomass for energy generation is clear, once it provides the rational use of the available resources, it also reduces the income transfer to other agents and decreases to the dependence upon external sources of energy. Therefore, the purpose of this work is to analyze the economic feasibility of project implementation for vehicular energy generation from animal waste in the watershed area of Lajeado Grande, in the city of Toledo, Paraná State. In order to achieve the objectives enabled in this work, it was carried out field and bibliographical research and 39 surveys were applied in each of the properties which rendered livestock management in the watershed of Lajeado Grande. The properties’ breeding stock of animals was up to 285.484 (swine, cattle and poultry), with a waste production on the potential of 85.024,07 m³/year and a biogas production potential of 1,569,608.39 m³/year. Accordingly, it was analyzed some of the possible uses of the biogas produced in the Lajeado Grande agricultural energy condominium,, instead of the natural gas – biomethane, and it was concluded over the positive feasibility, as based on the community features, upon the energy demanding stakeholders and as per the economic outcomes.